Dose reduction of biologics in patients with plaque psoriasis: a review - C. A. M. van Riel; C. A. M. van Riel; C. A. J. Michielsens; C. A. J. Michielsens; M. E. van Muijen; M. E. van Muijen; L. S. van der Schoot; L. S. van der Schoot; J. M. P. A. van den Reek; J. M. P. A. van den Reek; E. M. G. J. de Jong; E. M. G. J. de Jong; et al. (Frontiers Media S.A., 2024)
Dose reduction (DR) of first-generation biologics for plaque psoriasis (TNF-alpha inhibitors (i) and interleukin (IL)-12/23i) has been described in a previous scoping review. The literature on the DR of the newest generation of biologics (IL-17/23i) was scarce. The current review provides a literature update on the previous scoping review on the DR of all biologics, including the newest generation, with a focus on the uptake and implementation of DR in practice. The current literature search on DR revealed 14 new articles in addition to those in the previous review. Four of the newly found articles tested DR strategies, mostly focusing on first-generation biologics; only guselkumab (IL-23i) was included in one study. The other 10 studies showed data on regaining response after failure of DR, safety, cost-effectiveness, and uptake and implementation, as well as information about IL-17/23i. The eligibility criteria to start DR included both absolute and relative Psoriasis Area and Severity Index (PASI) scores (PASI ≤3/≤5/PASI 75-100) and/or Dermatology Life Quality Index (DLQI) ≤3/≤5, or BSA ≤1/≤2, or Physician Global Assessment (PGA) ≤1/0-2 during a period ranging from 12 weeks to ≥1 year. Most studies used PASI ≤5 and/or DLQI ≤5 or PGA ≤1 for ≥6 months. DR strategies were mostly performed by stepwise interval prolongation in two steps (to 67% of the standard dose, followed by 50%). Some studies of IL-17/23i reduced the dose to ±25%. The tested DR strategies on stepwise or fixed DR on TNF-αi and IL-12/23i (three studies), as well as one "on-demand" dosing study on IL-23i guselkumab, were successful. In the case of relapse of DR on TNF-αi and IL-12/23i, clinical effectiveness was regained by retreatment with the standard dose. All studies showed substantial cost savings with the biologic DR of TNF-αi and IL-12/23i. The identified barriers against the implementation of DR were mainly a lack of guidelines and scientific evidence on effectiveness and safety, and a lack of time and (technical) support. The identified facilitators were mainly clear guidelines, feasible protocols, adequate education of patients and physicians, and cost reduction. In conclusion, DR seems promising, but a research gap still exists in randomized, prospective studies testing DR strategies, especially of IL-17/23i, hampering the completion of guidelines on DR. Taking into account the identified barriers and facilitators most likely results in a more successful implementation of biologic DR in practice.